C[sbnd]C bond cleavage in the electrooxidation of 2,3-butanediol controlled by an ionic liquid modifier - Yang, Juntao; Haßfurther, Florian; Hilpert, Felix; Hussain, Zarah; Yang, Tian; Taccardi, Nicola; Wasserscheid, Peter; Brummel, Olaf; Libuda, Jörg (Journal of Catalysis, 2024)
In heterogeneous catalysis, ionic liquids (ILs) are used as chemical modifiers to control selectivity. In our work, we aim to apply the same concept to electrocatalytic systems. As a model reaction, we studied the electrooxidation of 2,3-butanediol on the low-index Pt(1 1 1), Pt(1 0 0) and Pt(1 1 0) surfaces in an acidic environment. We used the IL 1-ethyl-3-methylimidazolium trifluoromethanesulfonate ([C2C1Im][OTf]) dissolved in an aqueous electrolyte as a catalyst modifier. The reaction mechanisms were investigated by electrochemical infrared reflection absorption spectroscopy (EC-IRRAS). The oxidation of 2,3-butanediol is highly structure dependent. On all three surfaces, the two products formed are acetoin and diacetyl, i.e. either one or two alcohol functionalities are oxidized. However, we observe distinct features on the different surfaces with respect to activity, potential window of oxidation, and selectivity. Only the Pt(1 0 0) surface is active towards C[sbnd]C bond cleavage. The latter reaction leads to the formation of COads and poisoning of the catalyst. Modification of this surface by addition of the IL leads to an increase of the selectivity for acetoin from 51 % to 78 % (at 1.1 VRHE). In addition, C[sbnd]C bond cleavage is suppressed, no CO is formed, and the surface remains active for the target reaction. We attribute these effects to the reversible and structure dependent adsorption of the [OTf]− anions on the Pt surfaces and additional interionic interactions. Our results demonstrate the potential of ILs to control selectivity in electrocatalytic reactions.
CRIS-Team Scopus Importer:2024-05-31
Keywords: In-situ IR spectroscopy; Ionic liquids; Platinum; Secondary alcohols; Selectivity; Single crystals; Supported catalyst with ionic liquid layer

Increasing Activity of Trimetallic Oxygen Reduction PtNiMo/C Catalysts Through Initial Conditioning - Danisman, Bilal; Zhang, Gui Rong; Baumunk, Adrian F.; Yang, Juntao; Brummel, Olaf; Darge, Philipp; Dworschak, Dominik; Mayrhofer, Karl J.J.; Libuda, Jörg; Zhou, Xin; Wu, Mingjian; Spiecker, Erdmann; et al. (ChemElectroChem, 2024)
This study investigates the importance of preconditioning in Pt-alloy catalysts for oxygen–reduction reactions. Previous research indicated that slower scanning rates during preconditioning initially boost activity, but this is followed by a rapid decline. The study reveals the required number of cycles to achieve the first constant steady state activity in PtNiMo/C catalysts when using slower scanning rates during preconditioning. It also highlights the resulting activity differences. Remarkably, a catalyst preconditioned with 150 slow cycles showed an activity of approximately 1.25 mA cm−2 at 0.90 VRHE, significantly higher than one preconditioned at a fast rate (0.82 mA cm−2). Both ex–situ and in–situ analyses revealed that Pt, along with Ni, was leached during pretreatment. At slower scan rates of 20 mV s−1, the dissolved Pt redeposited as highly active, small-sized clusters or single atoms. Fast scan rates of of 500 mV s−1, in contrast, resulted in fewer such clusters. Accelerated stress tests up to 1.10 VRHE confirmed the high stability of these clusters, demonstrating a substantial activity increase even after 24,000 cycles.
CRIS-Team Scopus Importer:2024-03-29
Keywords: Accelerated Durability; Cyclic Voltammetry; Nanoparticles; Oxygen Reduction; Pretreatment

Interactions of the Ionic Liquid [C2C1Im][DCA] with Au(111) Electrodes: Interplay between Ion Adsorption, Electrode Structure, and Stability - Yang, Juntao; Hilpert, Felix; Qiu, Yunsheng; Franz, Evanie; Briega-Martos, Valentín; Cherevko, Serhiy; Mayrhofer, Karl; Brummel, Olaf; Libuda, Jörg (Journal of Physical Chemistry C, 2024)
Modification of electrocatalysts with ionic liquids (ILs) allows us to control the activity and selectivity on the one hand but also directly affects the stability of the electrode. In this work, we studied the interaction of the IL 1-ethyl-3-methylimidazolium dicyanamide [C2C1Im][DCA] with a Au(111) surface in an aqueous electrolyte (phosphate buffer, pH 7) and the impact of the IL on the electrochemical stability of the surface. We combined complementary electrochemical in situ methods, namely, electrochemical infrared reflection absorption spectroscopy (EC-IRRAS), cyclic voltammetry (CV), electrochemical scanning tunneling microscopy (EC-STM), and online inductively coupled plasma mass spectrometry. We observe the potential-dependent and reversible adsorption-desorption of ionic species on the Au(111) surface in the potential window between 0.1 and 1.1 VRHE. We identified two types of adsorbed [DCA]− species, showing different adsorption kinetics. Already at low concentrations, the IL (10 mM) enhances the dissolution during oxidation and reduction cycles by a factor of more than 40. We observe a suppressed redeposition of dissolved Au-ions in the presence of the IL due to the formation of gold complexes with the [DCA]− anions. Our result provides molecular insights into the interplay between ionic liquid-surface interactions and surface stability.
CRIS-Team Scopus Importer:2024-03-08

Modifying the Electrocatalytic Selectivity of Oxidation Reactions with Ionic Liquids - Yang, Tian; Yang, Juntao; Deng, Xin; Franz, Evanie; Fromm, Lukas; Taccardi, Nicola; Liu, Zhi; Görling, Andreas; Wasserscheid, Peter; Brummel, Olaf; Libuda, Jörg (Angewandte Chemie International Edition, 2022)
The "solid catalyst with ionic liquid layer" (SCILL) is an extremely successful new concept in heterogeneous catalysis. The idea is to boost the selectivity of a catalyst by its modification with an ionic liquid (IL). Here, we show that it is possible to use the same concept in electrocatalysis for the selective transformation of organic compounds. We scrutinize the electrooxidation of 2,3-butanediol, a reaction which yields two products, singly oxidized acetoin and doubly oxidized diacetyl. When adding the IL (1-ethyl-3-methyl-imidazolium trifluormethanesulfonate, [C(2)C(1)Im][OTf]), the selectivity for acetoin increases drastically. By in situ spectroscopy, we analyze the underlying mechanism: Specific adsorption of the IL anions suppresses the activation of water for the second oxidation step and, thus, enhances the selectivity for acetoin. Our study demonstrates the great potential of this approach for selective transformation of organic compounds.
CRIS-Team WoS Importer:2022-06-03

Origin of the Low Overpotential for Isopropanol Oxidation on Pt-Ru Electrocatalysts - Simanenko, Alexander; Samal, Pankaj Kumar; Hübsch, Robert; Škvára, Jan; Yang, Juntao; Kastenmeier, Maximilian; Winkler, Florian; Skála, Tomáš; Tsud, Nataliya; Mehl, Sascha; Mysliveček, Josef; Brummel, Olaf; et al. (ACS Energy Letters, 2024)
Electrochemically active liquid organic hydrogen carrier (EC-LOHC) technology is an emerging solution for safe and environmentally friendly hydrogen storage and energy conversion based on the use of organic redox-active compounds, such as the isopropanol/acetone couple. In this work, we identify the nature of the active state of the Pt-Ru electrocatalyst that provides the lowest overpotential and, thus, the highest catalytic activity. Toward this aim we employed ex situ electrochemical synchrotron radiation photoelectron spectroscopy (SRPES) and scanning tunneling microscopy (STM) in combination with in situ electrochemical infrared reflection absorption spectroscopy (EC-IRRAS). We show that the lowest overpotentials are not observed for Pt-Ru surface alloys but only in the presence of ultrasmall metallic Pt aggregates formed by dealloying of Pt-Ru catalysts upon oxidation and reduction cycles between 0.0 and 1.5 VRHE. By tuning the initial composition of the Pt-Ru surface alloy, we maximize the density of active Pt aggregates.
CRIS-Team Scopus Importer:2024-10-18

Strong Activity Changes Observable during the First Pretreatment Cycles of Trimetallic PtNiMo/C Catalysts - Danisman, Bilal; Zhang, Gui Rong; Baumunk, Adrian F.; Yang, Juntao; Brummel, Olaf; Darge, Philipp; Mayrhoferhttps, Karl J.J.; Libuda, Jörg; Ledendecker, Marc; Etzold, Bastian J.M. (ChemElectroChem, 2023)
Pt-based alloy catalysts supported on carbon are commonly characterized for oxygen reduction reaction (ORR) activity using the rotating disk electrode technique (RDE). Within this study, we show exemplarily for PtNiMo/C catalysts that the applied pretreatment influences strongly the determined activity. The classically employed descriptor of unchanged cyclic voltammetry response is insufficient to portrait completed surface restructuring, and gives an incorrect impression that stable activity can be determined. This might be one of the reasons for the strongly deviating activities reported in literature. Following the changes in activity during pretreatment also with in-situ FTIR and online dissolution measurements gives insights to an up to now largely overseen high activity of the trimetallic catalysts. A maximum activity of 0.57 mA cmPt−2 at 0.95 VRHE is reached quickly during the first six cycles and decreases slowly subsequently. The maximum activity and change of activity over the cycle number is affected by the scan rate and electrolyte refreshing, while the gas atmosphere plays only a minor role. This exemplary study might be important for Pt alloy catalysts in general.
CRIS-Team Scopus Importer:2023-08-15
Keywords: Alloyed Catalyst; Cyclic voltammetry; Electrochemistry; Oxygen Reduction; Pretreatment; Rotating Disk Electrode

The Influence of Ionic Liquid Modification on the Restructuring of Trimetallic PtNiMo/C Catalysts During Conditioning - Danisman, Bilal; Yang, Juntao; Zhang, Gui-Rong; Brummel, Olaf; Kovács, Miklós Márton; Dworschak, Dominik; Steffen, Julien; Ledendecker, Marc; Görling, Andreas; Mayrhofer, Karl; Libuda, Jörg; Etzold, Bastian (ChemElectroChem, 2025)
During preconditioning of PtNiMo/C catalyst metal dissolution and redeposition takes place. At slow scan rates this leads to increased steady activity for oxygen reduction reaction (ORR). Furthermore, ionic liquids (IL) influence the activity of Pt-based catalysts and can alter the leaching of Pt-alloy catalysts. This study investigates the influence of ILs on the preconditioning of PtNiMo/C catalysts. Therefore, preconditioning parameters as well as the IL employed were varied. ILs with long side chains like [C8fC1][BETI] resulted in a spreading of the activity development during preconditioning over a longer cycle time and with damped amplitude for the activity changes. For shorter side chains like [BMIM][BETI] the development is like the pristine catalyst. Ex-situ and in-situ characterization revealed that [BMIM][BETI] leached fast to the electrolyte, which was not observed for the other ILs. Nevertheless, for all ILs a strongly reduced platinum leaching was observed. Even for the leached [BMIM][BETI] a stable wetting layer influencing the leaching seems to remain. Nevertheless, only for the other ILs where an immobilized bulk phase is remaining a difference in catalyst restructuring during the preconditioning is observed and a higher number of small sized Pt clusters and a lower amount of bigger Pt clusters resulte
CRIS-Team Scopus Importer:2025-02-17
Keywords: Cyclic Voltammetry; Ionic Liquids; Nanoparticles; Oxygen Reduction; Pretreatment

Toward High-Energy-Density Fuels for Direct Liquid Organic Hydrogen Carrier Fuel Cells: Electrooxidation of 1-Cyclohexylethanol - Fusek, Lukáš; Briega-Martos, Valentín; Minichová, Maria; Fromm, Lukas; Franz, Evanie; Yang, Juntao; Görling, Andreas; Mayrhofer, Karl J.J.; Wasserscheid, Peter; Cherevko, Serhiy; Brummel, Olaf; Libuda, Jörg (Journal of Physical Chemistry Letters, 2024)
Electrochemically active liquid organic hydrogen carriers (EC-LOHCs) can be used directly in fuel cells; so far, however, they have rather low hydrogen storage capacities. In this work, we study the electrooxidation of a potential EC-LOHC with increased energy density, 1-cyclohexylethanol, which consists of two storage functionalities (a secondary alcohol and a cyclohexyl group). We investigated the product spectrum on low-index Pt single-crystal surfaces in an acidic environment by combining cyclic voltammetry, chronoamperometry, and in situ infrared spectroscopy, supported by density functional theory. We show that the electrooxidation of 1-cyclohexylethanol is a highly structure-sensitive reaction with activities Pt(111) ≫ Pt(100) > Pt(110). Most importantly, we demonstrate that 1-cyclohexylethanol can be directly converted to acetophenone, which desorbs from the electrode surface. However, decomposition products are formed, which lead to poisoning. If the latter side reactions could be suppressed, the electrooxidation of 1-cyclohexylethanol would enable the development of EC-LOHCs with greatly increased hydrogen storage capacities.
CRIS-Team Scopus Importer:2024-03-15